2019
DOI: 10.1093/humrep/dey393
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human granulocyte– colony stimulating factor in women with unexplained recurrent pregnancy losses: a randomized clinical trial

Abstract: STUDY QUESTION Does administration of recombinant human granulocyte colony stimulating factor (rhG-CSF) in the first trimester improve pregnancy outcomes, among women with a history of unexplained recurrent pregnancy loss? SUMMARY ANSWER rhG-CSF administered in the first trimester of pregnancy did not improve outcomes among women with a history of unexplained recurrent pregnancy loss. WHAT IS KNOWN ALREADY The only previous randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 17 publications
(20 reference statements)
0
21
0
1
Order By: Relevance
“…The authors observed that the use of subcutaneous G‐CSF (1 µg/kg/d) starting on the sixth day after ovulation significantly increases the number of live births in the treated group (29/35, 82.8%) compared with the control (16/33, 48.5%; OR: 5.1, 95% CI 1.5‐18.4, P = .0061) 45 . New studies evaluating the use of G‐CSF in cases of RM and patients undergoing assisted ART (in cases of thin endometrium or RIF) have also been published 46‐48 . G‐CSF can be administered via either the subcutaneous (SC) route or IU infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that the use of subcutaneous G‐CSF (1 µg/kg/d) starting on the sixth day after ovulation significantly increases the number of live births in the treated group (29/35, 82.8%) compared with the control (16/33, 48.5%; OR: 5.1, 95% CI 1.5‐18.4, P = .0061) 45 . New studies evaluating the use of G‐CSF in cases of RM and patients undergoing assisted ART (in cases of thin endometrium or RIF) have also been published 46‐48 . G‐CSF can be administered via either the subcutaneous (SC) route or IU infusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in serum G-CSF may not reflect local concentrations within the maternal-fetal interface and its paracrine/autocrine effects are likely to be more important for a contribution to the etiology of complications of pregnancy. Pre-conception administration of G-CSF may also be beneficial for a subset of women with recurrent pregnancy loss or recurrent implantation failure, although the mechanism of action is not yet fully understood ( Santjohanser et al, 2013 ; Eapen et al, 2019 ; Kamath et al, 2020 ; Rocha et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, three recombinant fusion proteins, consisting of sGCSF isoforms, were investigated and the results demonstrated that these confer a myelopoietic effect in response to oral delivery in a mouse model. Recombinant human and bovine fusion proteins have been reported to be effective for the development of oral vaccines or drug candidates (Eapen et al . 2019; Nguyen 1994; Stephens et al .…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant human GCSF transcript variant B has been commercially available since 1992 (Fraser et al . 1994); however, several unanswered questions need to be addressed by clinical trials (Eapen et al . 2019; Nguyen 1994).…”
Section: Introductionmentioning
confidence: 99%